Controllability-Oriented Placement of Actuators for Active Noise-Vibration Control of Rectangular Plates Using a Memetic Algorithm - WRONA, Stanisław; PAWEŁCZYK, Marek (Archives of Acoustics, 2013)
For successful active control with a vibrating plate it is essential to appropriately place actuators.One of the most important criteria is to make the system controllable, so any control objectives can beachieved.In this paper the controllability-oriented placement of actuators is undertaken. First, a theoreticalmodel of a fully clamped rectangular plate is obtained. Optimization criterion based on maximization ofcontrollability of the system is developed. The memetic algorithm is used to find the optimal solution.Obtained results are compared with those obtained by the evolutionary algorithm. The configuration isalso validated experimentally.